Influence of heat sources to finite channel conjugate natural convection of a power fluid - Quang, Vu Duy; Chung, Dang Huu (Vietnam Journal of Mechanics, 1995)
The paper extended the studies of Thomas F. Irvine et al. [1] and V. D. Quang and D. H. Chung [2] by considering the influence of heat transfer into the wall of vertical channel with natural convection motion of a power law fluid as well as the -influence of heat sources. The results obtained in s9me test cases showed that the influence of wall will be clear and impossible to neglect when thermal conductivity of wall is small enough, so the effect of heat source distributed in the fluid is more considerable than in the wall and the heat source from 50kW / m3 will make an effect more considerably.